Design of an Internet of Things-Based automatic cat feeding control device (IoT) - Al-Hafiz, Nofri Wandi; Harianja, Harianja (Jurnal Mandiri IT, 2024)
The automation era has been a big step in human civilization. The use of automation technology combined with an internet connection, or IoT, has helped a lot in everyday life. In one example, feeding cats is a problem when the owner is busy working or traveling for more than two days. However, having a cat feeding device is automatically a solution to this problem. This research created an automatic cat feeding device using the NodeMCU ESP8266 microcontroller base, which has a WiFi module installed. When it is paired with an HCR04 ultrasonic sensor to measure the feed height, it will send a message to the MQTT application on the smartphone if the remaining feed in the cat food container is at a certain height or is almost finished. The Blynk application manages this tool, which provides a widget to help monitor, change feeding times, view feeding statistics, and view the last feeding time and date. The black box testing method is used to test this tool so that it functions properly.